2009
DOI: 10.4161/auto.5.8.9825
|View full text |Cite
|
Sign up to set email alerts
|

Roles of mitophagy and the mitochondrial permeability transition in remodeling of cultured rat hepatocytes

Abstract: In primary culture, hepatocytes dedifferentiate, and their cytoplasm undergoes remodeling. Here, our aim was to characterize changes of mitochondria during remodeling. Hepatocytes were cultured one to five days in complete serum-containing Waymouth’s medium. In rat hepatocytes loaded with MitoTracker Green (MTG), tetramethylrhodamine methylester (TMRM), and/or LysoTracker Red (LTR), confocal microscopy revealed that mitochondria number and mass decreased by approximately 50% between Day 1 and Day 3 of culture.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
83
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(84 citation statements)
references
References 39 publications
1
83
0
Order By: Relevance
“…These factors include the stage of the cell cycle, the energetic requirements of the cells, the environmental effects on the redox balance of the cells, the stage of differentiation, and/or cell signaling mechanisms. 54,55 An accurate determination of the number of mtDNA copies per cell is technically difficult to achieve because both the number of mitochondria per cell and the number of mtDNA copies per mitochondrion vary. 56,57 Our analysis could only focus on the variability of mtDNA gene expression at the level of per sample, ignoring the details of expression variability at the level of per mtDNA copy.…”
Section: Discussionmentioning
confidence: 99%
“…These factors include the stage of the cell cycle, the energetic requirements of the cells, the environmental effects on the redox balance of the cells, the stage of differentiation, and/or cell signaling mechanisms. 54,55 An accurate determination of the number of mtDNA copies per cell is technically difficult to achieve because both the number of mitochondria per cell and the number of mtDNA copies per mitochondrion vary. 56,57 Our analysis could only focus on the variability of mtDNA gene expression at the level of per sample, ignoring the details of expression variability at the level of per mtDNA copy.…”
Section: Discussionmentioning
confidence: 99%
“…However autophagy is the only known cellular mechanism that can actually mediate the degradation of entire organelles. Selective mitochondrial autophagy was first described by the Lemasters laboratory (who also coined the term Bmitophagy^; Rodriguez- Enriquez et al 2004Enriquez et al , 2006Enriquez et al , 2009. Later, it was confirmed that, in specific types of mammalian cells, depolarized mitochondria are selectively degraded by mitophagy (Narendra et al 2008;Twig et al 2008).…”
Section: Mitophagy As a Quality Control Mechanism In Mammalian Cellsmentioning
confidence: 98%
“…autophagy and mitochondrial degradation (24,25), we tested this possibility and discovered that RCAN1-1L overexpression leads to induction of autophagy and significant mitochondrial loss.…”
mentioning
confidence: 99%